Variable Sampling Period Filter PLL for Distorted Three-Phase Systems - Carugati, Ignacio (2012)
This paper proposes a novel variable sampling period filter PLL (VSPF-PLL) for use in the general area of three-phase systems. It is based on the concept of variable sampling period, which allows to automatically adjust the sampling frequency to be  Npll times the line frequency. Conventional three-phase PLL are based on synchronous reference frames (SRF) to estimate the phase error between the PLL and the input signals. However, SRF transform fail when the voltage waveforms are distorted. In this proposal, a Sliding Goertzel Transform (SGT)-based filter is used in the loop to reject disturbances, such as unbalanced voltage and harmonics. It allows to detect the positive sequence present in the systems without errors. Characteristics of VSPF-PLL, including its mathematical model as well as steady state and dynamic responses, are discussed in this paper. The method is implemented in a digital signal processor (DSP) and tested using typical disturbances, such as frequency steps, unbalances, harmonics, saturation  and line-to-ground fault. Comparative simulations are performed between the proposed VSPF-PLL and some of the most common three-phase PLL described in the literature. Advantages of the proposed system over  the methods analyzed are also discussed. Structural simplicity, robustness and harmonics rejection are other attractive features offered by the proposed system.